Bio-fuel production from Martynia annua L. seeds using slow pyrolysis reactor and its effects on diesel engine performance, combustion and emission characteristics. (15th February 2021) - Kumar, R. Sathish; Sivakumar, S.; Joshuva, A.; Deenadayalan, G.; Vishnuvardhan, R.
Abstract: This research work is mainly focused on the extraction of biofuel from Martynia annua seed through a slow pyrolysis process and its utilization as an alternative fuel for the diesel engine. The various properties of biofuel were investigated and the suitability of blending with diesel was also investigated. The pyrolysis process was carried out using a fixed bed batch type reactor unit with an electrical heater after the sample has undergone a pre-treatment process. The pyrolysis process was carried out at 650 °C with a particle size of 250 μm and 3 h of reaction time. The physicochemical properties of pyrolysis oil produced were determined and reported. The produced pyrolysis oil was tested in a diesel engine at different proportions with diesel. From the experimental work, it was found that blend MAPO20 recorded the lowest BSEC at all loads among other blends and diesel. Blend MAPO20 produced the highest BTE of 30.77% which is 2.92% higher than diesel and blend MAPO40 produced BTE at par with diesel. Martynia annua seed pyrolysis oil can replace the petrodiesel up to 40% in an unmodified diesel engine without any major variation in performance and emissions. Highlights: New biofuel from Martynia annua seeds by pyrolysis process which is not yet reported in literatures has been produced. Physicochemical properties of the Martynia annua pyrolysis oil have been evaluated. Usability of Martynia annua pyrolysis oil as fuel for unmodified diesel engine has been studied. Successful replacement of 40% of diesel without compromise in engine performance has been noted. Reduction in CO and UBHC emission has been recorded.